ผลของรังสีแกมมาแบบเฉียบพลันต่อบานไม่รู้โรยลูกผสมพันธุ์กลายในสภาพปลอดเชื้อ - ตักเตือน สุเพ็ญวดี; เตชะศีลพิทักษ์ ธัญญะ; สุขประเสริฐ พัฒนา; พิริยะภัทรกิจ อนันต์; บาลลา นุชรัฐ (Thai Journal of Science and Technology, 2018)
Abstract Gomphrena is a flowering plant that currently is not popular for using as a potted plant because of its tall, straggly appearance, overgrowth and lack of flower color variation. However, it can bloom all year round, and is extremely easy to grow and tolerant to drought and heat. The objective of this study was to investigate the most appropriate doses of gamma radiation for inducing mutations in gomphrena hybrid. Nodes of gomphrena hybrid were sterilized and cultured on ½ MS medium. The plants were irradiated with acute gamma rays at 20, 40, 60, 80 and 100 grays, then subcultured until the M1V3 generation and transferred into the greenhouse for growing. The results showed that exposure to gamma radiation caused a reduction of plant growth with increasing radiation dose. The dose of gamma radiation at which half the plants died after 60 days (LD50(60)) was 51 grays. In gomphrena, gamma radiation at 60 grays caused the greatest reduction in plant height, internode length, number of roots and leaf size. Keywords: mutation breeding; irradiation; node